BS HD 60269-2 AMD2. Low-voltage fuses. Part 2. Supplementary requirements for fuses for use by authorized persons (fuses mainly for industrial application). Examples of standardized systems of fuses A to K (14th May 2021) - British Standards Institution,
No abstract available